PENGEMBANGAN SOFT SKILL PEMUDA DALAM DESAIN GRAFIS DAN KONTEN VIDIO POSITIF GUNA MENINGKATKAN KREATIVITAS SDM BERBASIS PRODUK DI DESA WISATA CINTA RAJA - Novianda, Novianda; Fadillah, Nurul; Akram, Rizallul; Pramanda, Ryan; Sabardi, Wiky (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Cinta Raja village is located in the East Langsa sub-district of Langsa city, has beautiful natural potential and is dubbed as a tourist village. Village youth utilize this situation by improving skills in graphic design such as making posters, invitations, flayers and videos that can be uploaded on YouTube and print social media. Participants in this activity were 15 village youth with each division of graphic design 8 people and video content 7 people, the results of this activity were to produce youth who were able to make graphic design and video editing using the canva and capcut applications. The youth were very enthusiastic about participating in the activity. After this activity, it is hoped that they will remain enthusiastic and improve their quality and later from the skills possessed by each youth, they can become entrepreneurial opportunities both personally and in groups. The results of the activity stated that all 15 participants were able to use the canva and capcut applications for graphic design and video content